2018
DOI: 10.3389/fimmu.2018.01319
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in T Cell Function Are Associated With Individuals at Risk of Mycobacterium abscessus Complex Infection

Abstract: The increasing global incidence and prevalence of non-tuberculous mycobacteria (NTM) infection is of growing concern. New evidence of person-to-person transmission of multidrug-resistant NTM adds to the global concern. The reason why certain individuals are at risk of NTM infections is unknown. Using high definition flow cytometry, we studied the immune profiles of two groups that are at risk of Mycobacterium abscessus complex infection and matched controls. The first group was cystic fibrosis (CF) patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…It was recently shown that in vitro blockade of PD-1 signaling enhanced MAC-specific IFN-γ production by T cells [25] and NK T cells of PTB patients [42], indicating that this inhibitory pathway also affects T cell functions during mycobacterial infection. Elevated CTLA-4 was also observed on CD4 + T cells in NTM infection [24]. Consistent with these reports, we found that PD-1 + CD4 + T cells and CTLA-4 + CD4 + T cells were more prevalent in patients with MAC-PD compared with that in control participants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was recently shown that in vitro blockade of PD-1 signaling enhanced MAC-specific IFN-γ production by T cells [25] and NK T cells of PTB patients [42], indicating that this inhibitory pathway also affects T cell functions during mycobacterial infection. Elevated CTLA-4 was also observed on CD4 + T cells in NTM infection [24]. Consistent with these reports, we found that PD-1 + CD4 + T cells and CTLA-4 + CD4 + T cells were more prevalent in patients with MAC-PD compared with that in control participants.…”
Section: Discussionsupporting
confidence: 91%
“…Antigen-stimulated blood cells from NTM-PD patients showed an elevated Treg population compared with that from control individuals [39]. Furthermore, Tregs were increased in the peripheral blood of cystic fibrosis NTM patients compared with that of controls [24]. Our study demonstrates that Tregs were increased in MAC-stimulated PBMCs of MAC-PD patients compared with that of control individuals, suggesting that the elevated levels of Tregs might suppress T-cell responses, thereby protecting MAC and playing a pathogenic role in MAC-PD.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A more comprehensive study, that used multiplexed bead-based assays to evaluate 22 cytokines in 24 MABS patients, showed reduced levels of IFNγ, IL-12, IL-4, and IL-13 and high levels of IL-17 and IL-23 in patients. A hi-dimensional flow analysis between individuals at risk and not at risk of MABS disease revealed immune exhaustion in T cells (CTLA-4) may be playing a role (98). These finding is similar to studies performed in MAC infection (93,95).…”
Section: The Immune Response In Pulmonary Ntm Infectionsupporting
confidence: 82%
“…Research priorities recommended in the US and UK include rapid diagnostic tools fast identification of infecting species (34) and simple and cheap screening tool to identify patients at risk (83,98,112). These are considered high impact research goals that would alert clinicians to at risk patients enabling faster initiation of appropriate treatment and ultimately, superior care.…”
Section: Recent Developments and Research Prioritiesmentioning
confidence: 99%